Uniaxial tension test of human-skin invivo - Wan Abas, W.A.B.; Barbenel, J.C. (1982)
The application of uniaxial tension in vivo is a common test method for investigating mechanical properties of the skin. This paper reports an investigation of the strain distributions on the skin surface produced by such a test method. The strains were shown to be non-homogeneous with major concentrations being present near the area of load application. At all sites within the test area, axial, lateral and shear strains were present but their magnitude depended both on their position within the test site and the overall extension. The axial and lateral strains were largest and most uniformly distributed within the area bounded by th loading tabs. The shear strains, however, were smallest in the are bounded by the tabs. The distribution of the three strains became similar if they were referred to the principal axes. The area of skin within the strained area became larger as the overall deformation increased because additional skin was recruited from the sites lateral to the strained area. The general form of the load/strain relations and lateral contractions were site- and extension-dependent, but were similar to those found in vitro.